Relationship between strength and agility in futsal players - Picanço, Luan Merseburger (2012)
Introduction and objective: The futsal has the muscular strength and agility as the main physical abilities required for its pratice, which are defined respectively as the ability to overcome considerable external resistance with large muscular effort and ability to change direction and/or movement in the shortest time. However, there are few studies involving these physical abilities as well as their integration. The aim of this study was to evaluate and correlate the physical strength and agility of futsal players and determine the contribution of strength in the determination of the speed. Materials and methods: The lower limbs neuromuscular fitness was evaluated by horizontal jump, with triple jump, squat test and isometric test in the wall. Agility was assessed ShuttleRun Agility Test (SRAT) and Illinois Agility Test (IAT). Results: Were found diferences between Sub15 and Sub17 with Sub13 in agility and jump tests, beyond significant correlations (p<0,001) between IAT and horizontal jump (r = -0,71) and IAT and triple jump (r= -0,73). Also were observed relationship between SRAT and horizontal jump (p≤0,001; r= -0,56) and between SRAT and triple jump (p<0,001; r= -0,63). It was found that IAT depends 47% of horizontal jump, while SRAT is explained 46% by the combination of triple jump and squat test. Discussion and conclusion: The agility performance can be predicted by power performance and this ability explain, alone, almost a half of the SRAT and IAT performance.